Bus Stops as a Tool for Increasing Social Inclusiveness in Smart Cities - Nápoles, Víctor Manuel Padrón; Páez, Diego Gachet; Penelas, José Luis Esteban; García, Germán García; Santacruz, María José García (Smart Cities, 2020)
In the last years, the concept of Smart City has moved from a predominantly technological perspective towards a more human based approach, where terms as sustainability and inclusiveness are presents and are part of a new concept referred as Human Smart Cities. In this context, the mobility of people and services represents one of the major challenges that cities must solve. Therefore, urban mobility policies must integrate new mobility needs as well as minimize the impact transportation has on the environment and the quality of life in our cities. Urban areas need to develop new sustainable urban mobility systems integrating traffic state, transport users demand, transport capacity providers, etc. These requirements involve the use of new techniques and methods as Big Data and IoT, but it is necessary to include a social component to ensure social inclusion and inclusiveness, sustainability and inclusiveness. In this paper, we describe some challenges regarding barriers to access new mobility systems and their relevant information. Therefore, we propose a smart bus stop taking into account cultural and socioeconomics characteristics of the transport users employing as a basis the access to information systems.